2002
DOI: 10.1364/ol.27.001013
|View full text |Cite
|
Sign up to set email alerts
|

Structural long-period gratings in photonic crystal fibers

Abstract: We report what is believed to be the first example of structural long-period gratings written in pure silica photonic crystal fibers (PCFs). The gratings are realized by periodic collapse of the holes of the PCF by heat treatment with a CO(2) laser. The resulting periodic hole-size perturbation produces core-to-cladding-mode conversion. These results can lead to a new family of structural all-fiber devices that use the unique properties of PCFs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
71
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(73 citation statements)
references
References 10 publications
0
71
0
2
Order By: Relevance
“…12,86,87 In contrast, CO 2 laser irradiation is a highly efficient, low cost technique for writing a LPFG in a pure-silica PCF without photosensitivity. 20,24,25,27 Kakarantzas et al 20,88 reported, as shown in Fig. 5, the first example of structural LPFGs written in pure-silica solidcore PCFs.…”
Section: B To Write Lpfgs In Solid-core Pcfsmentioning
confidence: 96%
See 3 more Smart Citations
“…12,86,87 In contrast, CO 2 laser irradiation is a highly efficient, low cost technique for writing a LPFG in a pure-silica PCF without photosensitivity. 20,24,25,27 Kakarantzas et al 20,88 reported, as shown in Fig. 5, the first example of structural LPFGs written in pure-silica solidcore PCFs.…”
Section: B To Write Lpfgs In Solid-core Pcfsmentioning
confidence: 96%
“…The resulting periodic hole-size perturbation produces core-tocladding-mode conversion, thus creating a novel LPFG in the PCF. 20 This technique, combining with periodic mechanical twisting, can be used to fabricate a rocking filter in a polarization-maintaining ͑PM͒ PCF. 88 As shown in Fig.…”
Section: B To Write Lpfgs In Solid-core Pcfsmentioning
confidence: 99%
See 2 more Smart Citations
“…Photonic crystal fibre (PCF) might offer great potential in this regard since the waveguiding properties can be controlled simply by adjusting the air-hole geometry. Recently, it has been shown that LPGs can be produced in nonphotosensitive PCF by periodically collapsing the holes by heat treatment with a CO 2 laser [2] or by using an electric arc to modify the fibre structure [3]. In this paper we report the first experimental characterisation of the sensitivity of an electric arc-induced LPG in PCF to temperature, bending and strain.…”
mentioning
confidence: 90%